Long-Term Effect of Metformin on Metabolic Parameters in the Polycystic Ovary Syndrome - Cheang, Kai I. (2009)
Insulin resistance is a central feature of the polycystic ovary syndrome (PCOS) and may increase cardiovascular risk. Due to insulin resistance, the metabolic syndrome is more prevalent in PCOS women compared to normal women. Metformin improves the metabolic profile in PCOS in short-term studies. In this study, we evaluated the long-term effect of metformin on metabolic parameters in PCOS women during routine care without a controlled diet. We performed a retrospective medical chart review of 70 women with PCOS receiving metformin from an academic endocrine clinic. Metabolic risk factors were compared before and after metformin treatment. Time trends of these metabolic parameters were also analyzed. After a mean follow-up of 36.1 months with metformin treatment, improvements were observed for BMI (−1.09±3.48 kg/m(2), p=0.0117), diastolic blood pressure (−2.69±10.35 mmHg, p=0.0378), and HDL cholesterol (+5.82±11.02 mg/dL, p<0.0001). The prevalence of metabolic syndrome decreased from 34.3% at baseline to 21.4% (p=0.0495). The course of BMI reduction during metformin treatment was significantly more pronounced in PCOS women with metabolic syndrome at baseline, compared with those without the metabolic syndrome (p=0.0369 for interaction). In conclusion, metformin improved the metabolic profile of PCOS women over 36.1 months, particularly in HDL cholesterol, diastolic blood pressure and BMI.